Association analysis in linseed (Linum usitatissimum L.): ASSOCIATION ANALYSIS IN LINSEED - VIPIN KUMAR SINGH; S A KERKHI; PRAKRITI TOMAR; G P DIXIT (Journal of Oilseeds Research, 2019)
The present study was taken up to work out correlation coefficient among the various yield and yield related traits and to estimate direct and indirect effect of different traits on grain yield through path analysis in linseed. Forty diverse linseed genotypes were assessed for different traits in a field experiment. Correlation as well as path coefficient analysis were calculated among the traits. Association analysis revealed that seed yield/plant showed the highest and significant positive association with biological yield/plant, number of capsules/plant, harvest index, 1000-seed weight and number of secondary branches/plant. Path coefficient analyses, at genotypic and phenotypic level, indicated the significant direct and indirect effects of the traits on yield.